Revitalization of Furudul 'Ainiyah Learning to Improve Students' Religious Understanding - Rawasiyah Rawasiyah; Sugiono Sugiono (Indonesian Journal of Education and Social Studies, 2025)
This study aims to examine the revitalization of Furudul ‘Ainiyah learning as a strategy to improve the religious understanding of students in the Az-Zainiyah area of Pondok Pesantren Nurul Jadid Paiton. Furudul ‘Ainiyah includes the fundamental religious obligations that every Muslim must know, such as purification, prayer, fasting, and daily life etiquette, yet traditional monotonous learning methods tend to restrict students’ understanding to theoretical aspects. Using a descriptive qualitative approach through observation, interviews, and documentation, with data analyzed through reduction, presentation, and conclusion drawing, this study found that the revitalization of Furudul ‘Ainiyah learning had a positive impact on students’ religious understanding. Students not only better understood the basic concepts of worship but also practiced them consistently in their daily lives. Moreover, the learning process became more active, interactive, and meaningful, thereby strengthening students’ religious identity within the pesantren environment. The findings indicate that the revitalization of Furudul ‘Ainiyah learning can serve as an effective model for developing pesantren education in improving the quality of students’ religious understanding.